KESALAHAN BERBAHASA INDONESIA DALAM TESIS MAHASISWA PROGRAM STUDI MANAJEMEN PENDIDIKAN PASCASARJANA UNIMA TAHUN 2008 - Greis M. Rantung (Kadera Bahasa, 2011)
This study is aimed to (1) describe the spelling errors in usage and the error forms indiction of Pos-Graduate students thesis of Manado State University in Education Management Program 2008 and (2) describe the error forms in the diction of Unima Post-Graduate student thesis in Education Management Program 2008. This research descriptive with the following three stages, namely: (I) data provision stage, (2) data analysis stage, and (3) presenting the data analysis stage. The method in analysis speaking error method. The dominant error in spelling is the writing of unstandardized words, and the using of the word pairs or correlative conjunctions in diction are also complicated.